Integrasi Filsafat, Pancasila dan Teologi dalam Masyarakat Majemuk - Luciana Haryanto; Daniel Suharto (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Indonesia’s diversity in ethnicity, culture, religion, and language demands an approach that can simultaneously address intellectual, spiritual, and national dimensions. The integration of philosophy, Pancasila, and theology becomes essential in responding to this complex reality. Philosophy strengthens critical and reflective thinking, helping individuals interpret differences with awareness and avoid hasty judgments, which is crucial in reducing social tension and fostering dialogue. Pancasila, as the nation’s ideological foundation, provides an ethical-political framework that guarantees unity, freedom, and justice for all citizens regardless of background. Theology complements these foundations by offering transcendental ethics and spiritual guidance that shape compassionate attitudes toward others and the environment. A contextual and inclusive theological perspective supports religion’s role as a source of enlightenment and encourages interfaith solidarity in a pluralistic society. When these three elements are integrated into education, public policy, and social culture, they help form a society that is intellectually critical, socially inclusive, and spiritually resilient. Core values such as empathy, justice, equality, and shared responsibility can develop more strongly in daily interactions. Although challenges such as identity crises, misinformation, and online intolerance remain, collaboration between the state and civil society is needed to maintain an inclusive public sphere. Through strengthening philosophical education, deepening appreciation of Pancasila, and advancing contextual theology, Indonesia can build a just and harmonious society.